CXCR1 blockade selectively targets human breast cancer stem cells in vitro and in xenografts - Christophe Ginestier; Suling Liu; Mark E. Diebel; Hasan Korkaya; Ming Luo; Marty Brown; Julien Wicinski; Olivier Cabaud; Emmanuelle Charafe-Jauffret; Daniel Birnbaum; Jun-Lin Guan; Gabriela Dontu; et al. (The Journal of Clinical Investigation, 2010)
Recent evidence suggests that breast cancer and other solid tumors possess a rare population of cells capable of extensive self-renewal that contribute to metastasis and treatment resistance. We report here the development of a strategy to target these breast cancer stem cells (CSCs) through blockade of the IL-8 receptor CXCR1. CXCR1 blockade using either a CXCR1-specific blocking antibody or repertaxin, a small-molecule CXCR1 inhibitor, selectively depleted the CSC population in 2 human breast cancer cell lines in vitro. Furthermore, this was followed by the induction of massive apoptosis in the bulk tumor population via FASL/FAS signaling. The effects of CXCR1 blockade on CSC viability and on FASL production were mediated by the FAK/AKT/FOXO3A pathway. In addition, repertaxin was able to specifically target the CSC population in human breast cancer xenografts, retarding tumor growth and reducing metastasis. Our data therefore suggest that CXCR1 blockade may provide a novel means of targeting and eliminating breast CSCs.